Dicerto, S. (2018). Multimodal pragmatics and translation: A new model for source text analysis. London: Palgrave Macmillan. - Jiang, Zhanhao; Tao, Yuan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
Book review